Belief in God in an age of science - Polkinghorne, J. C., 1930-2021. (New Haven, CT : Yale University Press, 1998)
In this book, the author focuses on the collegiality between science and theology, contending that these "intellectual cousins" are both concerned with interpreted experience and with the quest for truth about reality. He argues eloquently that scientific and theological enquiries are parallel.
Belief in God in an age of science -- Finding truth: science and religion compared -- Does God act in the physical world? -- The continuing dialogue between science and religion -- Critical realism in science and religion -- Mathematical postscript.
The first four chapters are based on the Terry Lectures, which the author gave at Yale University in Oct. 1996.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Religion and science; Religion and Science; Religion et sciences; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Religion and science